The Critical Role Of Accounting Mentality In Enhancing Land And Building Tax (PBB) Compliance - Casia Chiquitita; Yopy Junianto (UNIVED Press, 2025)
This study aims to identify the factors influencing taxpayer compliance in paying Land and Building Tax (PBB) in Malang, Yogyakarta, and Denpasar. A closed-ended questionnaire was used in this study to investigate to find out how tax payer’s tax literacy, accounting mentality, and views on sanctions influence their tax compliance behavior. The influence of accounting mentality on PBB compliance remains underexplored. Existing research has yet to provide a comprehensive understanding of this relationship, leaving a clear opportunity for further investigation. Through a multiple linear regression of 258 respondents, this study found that accounting mentality has the most significant influence on PBB compliance. In addition, tax literacy and perception of tax sanctions also have a positive and significant impact. These findings have practical implications for city governments in efforts to improve PBB compliance through increasing tax literacy, strengthening accounting mentality, and enforcing strict and fair tax sanctions. Theoretically, these findings support the Theory of Planned Behavior, where tax literacy, accounting mentality, and perception of tax sanctions can influence taxpayer compliance behavior. This research also contributes to the existing literature by providing up-to-date findings on the relationship between these variables in the context of PBB compliance.